Generation Z's understanding of development sustainability in Indonesia through the perspective of intellectual intelligence - Ufi Rumefi (Annals of Management and Organization Research, 2025)
Purpose: The purpose of this study is to determine the contribution of Generation Z to sustainable development in Indonesia, which is based on intellectual intelligence. Research Methodology: The method used in this study was a descriptive quantitative method that distributes questionnaires. The target of the questionnaire was Generation Z in the Pasuruan district area, which was carried out using random sampling so that as many as 214 respondents were obtained. This study also used the WarpPLS version 22. Results: The results of this study show that Generation Z, who are intelligent and environmentally conscious, can be the main driver in achieving sustainable development goals in Indonesia. The existence of those who are active and concerned about environmental issues helps create a society that is more aware of the importance of protecting and preserving the environment for future generations. Conclusions: It can be concluded that with a deep understanding of environmental ethics, Generation Z can influence various aspects of life, including education, business, and public policy. Limitations: This research is limited to the 2023 research year is limited to the independent variable Environmental Ethic, the dependent variable Sustainable Development and to the mediating variable Intellectual Intelligence, the respondent is Gen Z in the Pasuruan regency area.. Contribution:  This study examines the role of Gen Z in realizing sustainable development from the perspective of intellectual intelligence. The study also identified the phenomenon of generation z unemployment in the last two years, which can slow down the sustainability of development in Indonesia by weakening purchasing power, so that the economic growth rate will decline. Novelty: This study uses environmental ethics as a variable. This study explored the variables of sustainable development, intellectual intelligence, and environmental ethics in generation z. The use of this environmental ethics variable can provide new information about individual awareness and the role of generation z in sustainable development.